Identification of verbs in a short film Pasport Ekspres - Abd Rahim, Normaliza ("Vasile Goldis" University Press, 2013)
This study focuses on the use of verbs in a short film. The objectives of the study were to identify and discuss the verbs presented in a Malay short film 'Pasport Ekspres'. The samples of the study consisted of 10 male and female subjects from a Malay language class at a university in Korea. The subjects were second year students majoring in the Malay-Indonesian language. The subjects were divided into groups of three. They were given 2 days to watch the film and then to identify and discuss the verbs in the film. After two days, the subjects were interviewed in groups. Each verb that they state had to have some evidence from the film. The results of the study revealed that the three groups managed to successfully identify and provide evidence of the verbs in the film. It is hoped that future studies will focus on the identification of verbs in Malay cartoons.